The ubiquitin-proteasome system in circadian regulation - Kara M. Costanzo; Matthew V. Prifti; Sokol V. Todi; Sokol V. Todi; Ryan D. Mohan (Frontiers in Neuroscience)
To align sleep–wake behavior and internal physiology with the Earth’s 24-h light–dark cycle, organisms rely on circadian clocks–endogenous timekeeping systems that anticipate and adapt to daily environmental changes. These clocks are governed by transcription-translation feedback loops that produce rhythmic oscillations in gene expression, including key regulators such as PERIOD and CRYPTOCHROME. The timing and stability of these proteins are tightly controlled by post-translational mechanisms, including ubiquitin-mediated degradation. The ubiquitin-proteasome system (UPS) ensures that clock proteins are cleared at precise times within the circadian cycle, a process which is essential for resetting the molecular clock and sustaining robust circadian rhythms. Disruption of this process can have profound impacts on human health and contribute to impairments in sleep timing, circadian phase, and rhythm amplitude. In this review, we focus on the mechanistic role of the UPS in circadian clock regulation, summarize key E3 ligases and deubiquitinating enzymes implicated in clock protein turnover, and highlight the essential role of the UPS on sleep timing and overall circadian biological homeostasis.